Longitudinal Distribution and Morphometric Character of Eel at the Downstream Site of Kabur River, East Likupang, North Minahasa - Hartanto, Frengky; Bataragoa, Nego E.; Lohoo, Anneke V. (Jurnal Ilmiah PLATAX, 2015)
Eel is a unique organism that grows in the freshwater habitat and when they have reached adult stage of life they will migrate thousands of kilometers to the sea for spawning. This research was aimed at identifying the eel species, defining the breadth composition of longitudinal distribution, describing and analyzing the relationship between length and weight (alometric, isometric growth) and the conditional factors, and determining the feeding habit of eels hauled in Kabur river, Rinondoran village, East Likupang District, North Minahasa Regency, North Sulawesi Province. The samples have been collected in April 19th 2015 based on the river length survey method. The hauling process was started at the downstream site which then headed to the upstream. The result of the research showed that there were two (2) species of eel that have been hauled they are Anguilla marmorata and Anguilla celebesensis. The value of F-count < F-table so the H0 is acceptable. It means that there is no difference in the size of eels in terms of their growing sites along the river. b value is 3,19217 so the growing pattern of A. marmorata in Kabur river is positive alometric ( b > 3 ). The average condition factor of every class of the total A. marmorata length is from 0,1691 to 0,2426. In general, the kinds of food usually consumed by the eels are shrimp, worm, and crab. Based on the index of preponderance, the highest percentage of diet is crab. Therefore, crab becomes the main diet with IP value of 78,2. Keywords: Eel, size, growth, conditional factor, feeding habit   A B S T R A K   Sidat adalah organisme unik yang bersifat katadromous yaitu tumbuh di habitat air tawar dan ketika dewasa akan bermigrasi ribuan kilometer untuk mengadakan pemijahan di laut. Penelitian ini bertujuan yaitu mengidentifikasi spesies sidat, menentukan komposisi ukuran sebaran longitudinal, mendeskripsikan dan menganalisis hubungan panjang berat (pertumbuhan alometrik, isometrik) serta faktor kondisi, menentukan kebiasaan makanan sidat yang tertangkap di Sungai Kabur, Desa Rinondoran, Kecamatan Likupang Timur, Kabupaten Minahasa Utara, Provinsi Sulawesi Utara. Pengambilan sampel dilakukan pada tanggal 19 april 2015 berdasarkan metode survei sepanjang sungai. Penangkapan di mulai dari hilir sampai menuju hulu sungai. Hasil penelitian menunjukkan bahwa ada dua spesies yang tertangkap yaitu Anguilla marmorata dan Anguilla celebesensis. Nilai F-hitung < F-tabel maka H0 diterima.  Ini berarti tidak terdapat perbedaan ukuran sidat pada tempat di sepanjang sungai.  Nilai b adalah 3,19217 jadi pola pertumbuhan A. marmorata di Sungai Kabur adalah allometrik positif (b > 3).  Nilai faktor kondisi rata – rata pada masing - masing selang kelas panjang total A. marmorata yaitu dengan kisaran antara 0,1691 - 0,2426. Secara keseluruhan makanan yang paling sering dijumpai pada lambung A. marmorata adalah udang, cacing, dan kepiting. Berdasarkan nilai indeks bagian terbesar (Indeks of Preponderance), persentase tertinggi terdapat pada jenis makanan yang berupa kepiting, dengan demikian kepiting menjadi makanan utama dengan nilai IP yaitu 78,2.   Kata Kunci : Sidat, ukuran, pertumbuhan, faktor kondisi, kebiasaan makanan 1Mahasiswa Program Studi MSP FPIK-UNSRAT 2Staf pengajar Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi